The impact of cultural activities on community building - Šeštokaitė, Severina; Kisieliauskas, Justinas (Socialiniai tyrimai, 2021)
This paper presents an analysis of the impact that cultural activities have on community building. Recently, more and more people begin to understand the importance of community: they bring about local communities, and they begin to get involved in its activities. Cultural activities, in this case, offer a significant assistance. They are regarded as part of a typical community building stage. In this paper, the local community is perceived as a localized, cohesive social group with its own traditions, established norms, values, share the same interests, place of residence or attendance, and the most important – emotional connection. Community building begins with a motivated human leader, then leader create a group of people, that is next step on community building, and then community influenced by cultural activities and other motives is building. Cultural activities, joint celebrations have a huge impact on community building; therefore, there is a legitimate reason for further considerations. Different art projects worldwide are flexible and bring results, furthermore, they are economically effective ways to solve community building problems. The experts substantiate the cultural activity benefits for the community and confirm the importance of a leader at the primary stage of community building.The object of this thesis is a the impact of cultural activities on community building.The goal of this thesis is after a theoretical analysis of the relationship between cultural activities and the community, to carry out a study to assess the formation of the community through cultural activities.Cultural regions of Lithuania are experiencing the decline in population which results in the decline of supply of cultural activities and activities related to arts. In the context of dwindling communities and eroding communality a research question of this thesis arises: how to build a community based on cultural activities?Research methods of this thesis include different types of methods. In the first chapter a comparative theoretical analysis and synthesis of sources of literature method is used. In this part of thesis, the concepts of culture and community, the impact of cultural activities on society and community building are examined.In the second chapter of this thesis, having the intention to receive practical advice, and to acquire know-how on event planning for communities, a qualitative method has been chosen in a form of semi-structured interview with representatives of communities in Šilainiai (Kaunas microdistrict), Balsiai (in Šilalė distr.) and Akademija (in Kaunas distr.). After finishing the process of analysis of and structuring all the results of quantitative research indicate: has revealed such results: communities form for different reasons, and they face similar challenges (lack of human and financial resources), communality is expressed differently in each community, and the events are being held in accordance with the needs of the respective community.The following conclusions are published after analyzing the impact of cultural activities on the community building theoretically and qualitative studies with community presidents-experts:• The community is a group of people connected by common interests, places, communications, but the most important thing is the feeling. When we talk about the local community, we need to perceive it as a localised group of people.• In community building activities, the classic path takes place through cultural activities. Artistic cultural phenomena create more cohesive and sustainable communities, making it easier to involve people in the community. There are many art projects around the world that seek to bring divisive societies into communities through cultural activities. Such projects are flexible, proven and cost-effective ways to address community development problems.After reviewing the collected interview material, the following recommendations can be made for those who want to build a community in their place:• At the beginning of the community building, it is important person-leader with enthusiasm, energy and charisma. The leader can‘t be to strong – have just his ideas, his vision. The good leader for community is person, who can accept other ideas, who can listen community wishes, needs and say thank you to community members. It is small thing that humans needs.• It is important for people that their wishes, needs, ideas are heard and to be allowed to implement them;• It is worth involving members of the community in the process of organizing events – it is important for them to feel necessary and useful, but after involving the community, the process of organizing takes longer. And here comes challenge for leader to be able to properly moderate and distribute the work for community;• It is very important to co-create the process with community, to communicate, let them to feel like the creators of the celebration;• The number of cultural activities to be organised varies according to the needs of the community, but it is important to maintain a cyclicality, quantity and quality ratio. It is worth having a few bigger celebrations for the whole community with a variety of activities, while other events are organized for smaller and target audiences. Activities must be non-binding, but innovative, modern and;• The community is made up of people of all ages and none of them should be forgotten – everyone has to find the right activities for themselves, but young mothers and seniors usually join communities, so at the beginning of the community it is the target audience to which cultural activities must be adapted;• News about community events works best in a word-of-mouth format, but all possible channels need to be used to invite people to events: networks, local newspapers, libraries or even churches.Every community is unique and you need to know or make research to getting know what is community wishes, needs, what ideas have community members. The leader must be person that community trust.
Keywords: community; cultural activities; community building; communality